Development of a solid-phase extraction with capillary liquid chromatography tandem mass spectrometry for analysis of estrogens in environmental water samples - Kozlík, Petr; Bosáková, Zuzana; Tesařová, Eva; Coufal, Pavel; Cabala, Radomír (Journal of chromatography. A, 2011)
Capillary liquid chromatography (cLC) hyphenated with tandem mass spectrometry (MS-MS) was used to separate and quantitate trace concentrations of five estrogens in aqueous samples. New C(18)-based sorption materials bound to the silica support by monomeric and polymeric mechanisms were compared and tested for solid-phase extraction (SPE) of selected analytes with respect to optimization of their preconcentration yield. Application of an endcapped, monomer-bound preconcentration Discovery DSC-18Lt column under the optimized conditions provides yields in the range from 95 to 100% with a high repeatability (n=3, RSD≤7.2%). Using the electrospray ionization in the positive mode (ESI+), the cLC-MS-MS system (the Zorbax SB C18 capillary column and a binary mobile phase of acetonitrile and water containing 0.1% formic acid in both the components) was optimized to attain a sufficient retention of the early eluting estriol, a satisfactory resolution of the analytes and the maximum sensitivity of the determination. Both the isocratic and gradient elution were used and the optimized gradient method permitted analyses of aqueous environmental samples in 14 min within a linearity range from 6.1 to 25.0 (LOQ of analytes) to 500 ng/L and with a very good linearity (r>0.9981) for all the estrogens studied. The detection limits are in the range from 3.0 to 6.8 ng/L (1 μL injection volume). Six environmental water samples were analyzed and the studied estrogens were found in the Vltava river sample collected in Prague (13.2 ng/L for 17β-estradiol) and in the inlet to the wastewater treatment plant in Prague, at an overall concentration of 371.4 ng/L.
Keywords: Reproducibility of Results; estrogeny; reprodukovatelnost výsledků; Capillary Electrochromatography; lineární modely; Sensitivity and Specificity; řeky; Rivers; chemické látky znečišťující vodu; extrakce na pevné fázi; Linear Models; Water Pollutants, Chemical; Tandem Mass Spectrometry; Estrogens; senzitivita a specificita; tandemová hmotnostní spektrometrie; hmotnostní spektrometrie s elektrosprejovou ionizací; kapilární elektrochromatografie; Spectrometry, Mass, Electrospray Ionization; Solid Phase Extraction